Correlation Between Parenting Styles During The COVID-19 Pandemic with The Level of Personal Social Development of Preschool Children (3-6 Years) - Harahap, Rahmaini Fitri; Manullang, Marito; Butar-Butar, Nurul Hajah; Nurfida, Nurfida (Journal of Maternal and Child Health, 2022)
Background: The golden period (Golden Age) is the maturation of psychic and physical functions that respond to environmental stimuli and incorporate them into their personality. Child development is an important aspect that must be optimized in preschool, especially in the personal social aspect. Parenting patterns greatly determine the social activities of children in their development stage. This study aims to see the relationship between parenting patterns during the COVID-19 pandemic with the level of social development of preschool children (3-6 years). Subjects and Method: This research is an analytical observational study with a cross sectional design at Ummi Erni Kindergarten Pematang Johar on Friday, November 19, 2021. 30 subjects were selected by the total sampling method. The dependent variable is the level of child development. The independent variable is parenting. Data were analyzed by chi-square test. Results: From 30 subjects, it can be seen that there are 25 positive parenting styles with normal child development (83.3%), negative parenting patterns with suspected child development as many as 5 people (16.7%). This study shows that there is a significant relationship between parenting patterns and personal social development of preschool children (3-6 years) (p < 0.001). Conclusion: Parenting patterns are related to the personal social development of preschool children (3-6 years) at Ummi Erni Kindergarten, Pematang Johar Village.